Types of political connections, election years, and firm performance in Pakistan: Moderating role of external monitoring - Muhammad Saif Ul Islam; Woei-Chyuan Wong; Mohd Yushairi Bin Mat Yusoff (Cogent Business & Management, 2023)
The study aims to examine the impact of different types of political connections in Pakistan on the performance of firms. We further examine whether the presence of external monitors, such as foreign and institutional investors, can moderate the impact of political connections on the performance of firms in Pakistan. In addition, we explore the association between political connections and firm performance during election and non-election years. This study uses 2479 firm-year observations for firms listed on the Stock Exchange of Pakistan from 2010 to 2019 as the final sample and uses regression to test the hypotheses. The findings of this study show that political connections are negative and strongly significant across all three performance indicators, such as ROA, ROE, and Tobin's Q, indicating that political connections can harm firm value. Further analyses indicate that the detrimental impact of political connections on firm performance is attributable to CEOs who have political connections and is more pronounced during general election years in Pakistan. The findings further report some weak evidence of the monitoring roles played by foreign and institutional in mitigating the negative impact of political connections. Policymakers in Pakistan, therefore, ought to design stricter disclosure measures to limit the potential wealth expropriation in politically connected firms, given the lack of shareholder activism by outside shareholders in this country. Our results further suggest that external monitors, such as foreign and institutional ownership, play a relatively limited role in mitigating the adverse impact of political connections on the performance of firms.
Keywords: 650; connected CEO; connected chairman; election years; external monitoring; non-election years; performance of firm; Political connections